The Regulation of Continuous Election Design’s Implementation Based on the Constitutional Court’s Decision - Aufa Naufal Rishanda (Constitutionale, 2021)
This study aims to describe the consistency of judges' considerations in the Constitutional Court Decision No. 14/PUU-XI/2013 and the Constitutional Court Decision No. 55/PUU-XVII/2019 and its suitability with the design of the election administration according to the 1945 Constitution of the Republic of Indonesia. To measure the consistency of the two Constitutional Court Decisions, the meaning of the original intent of holding elections simultaneously according to the Amendment of the 1945 Constitution of the Republic of Indonesia will be used. This is normative legal research, which uses approach legislation (statute approach) and historical approach (historical approach). The results of this study indicate that the judge's considerations in the Constitutional Court Decision 14/PUU-XI/2013 are inconsistent with the Constitutional Court Decision 55/PUU-XVII/2019. Based on the original intent study, the Amendrs to the 1945 Constitution of the Republic of Indonesia disagreed on the simultaneous implementation of the General Election in Indonesia. So the judge's consideration in the Constitutional Court's decision Number 14/PUU-XI/2013, which requires simultaneous elections, is not following the design of the election administration according to the amendment to the 1945 Constitution of the Republic of Indonesia. Six alternatives for the simultaneous implementation of elections.